ClNO2 Yields From Aircraft Measurements During the 2015 WINTER Campaign and Critical Evaluation of the Current Parameterization. Issue 22 (25th November 2018) - McDuffie, Erin E.; Fibiger, Dorothy L.; Dubé, William P.; Lopez Hilfiker, Felipe; Lee, Ben H.; Jaeglé, Lyatt; Guo, Hongyu; Weber, Rodney J.; Reeves, J. Michael; Weinheimer, Andrew J.; Schroder, Jason C.; Campuzano‐Jost, Pedro; et al.
Abstract: Nitryl chloride (ClNO2 ) plays an important role in the budget and distribution of tropospheric oxidants, halogens, and reactive nitrogen species. ClNO2 is formed from the heterogeneous uptake and reaction of dinitrogen pentoxide (N2 O5 ) on chloride‐containing aerosol, with a production yield, ϕ (ClNO2 ), defined as the moles of ClNO2 produced relative to N2 O5 lost. The ϕ (ClNO2 ) has been increasingly incorporated into 3‐D chemical models where it is parameterized based on laboratory‐derived kinetics and currently accepted aqueous‐phase formation mechanism. This parameterization models ϕ (ClNO2 ) as a function of the aerosol chloride to water molar ratio. Box model simulations of night flights during the 2015 Wintertime INvestigation of Transport, Emissions, and Reactivity (WINTER) aircraft campaign derived 3, 425 individual ϕ (ClNO2 ) values with a median of 0.138 and range of 0.003 to 1. Comparison of the box model median to those predicted by two other field‐based ϕ (ClNO2 ) derivation methods agreed within a factor of 1.3, within the uncertainties of each method. In contrast, the box model median was 75–84% lower than predictions from the laboratory‐based parameterization (i.e., [parameterization − box model]/parameterization). An evaluation of factors influencing this difference reveals a positive dependence of ϕ (ClNO2 ) on aerosol water, opposite to the currently parameterized trend. Additional factors may include aqueous‐phase competition reactions for the nitronium ion intermediate and/or direct ClNO2 loss mechanisms. Further laboratory studies of ClNO2 formation and the impacts of aerosol water, sulfate, organics, and ClNO2 aqueous‐phase reactions are required to elucidate and quantify these processes on ambient aerosol, critical for the development of a robust ϕ (ClNO2 ) parameterization. Key Points: Box modeling of wintertime measurements over the eastern United States provides the first determinations of ClNO2 yields ( ϕ (ClNO2 )) from aircraft The median ϕ (ClNO2 ) value derived from the box model is overpredicted by 75‐84% by the current laboratory‐based ϕ (ClNO2 ) parameterization Modeled and parameterized ϕ (ClNO2 ) values show opposite trends with aerosol water, suggesting an incorrectly parameterized dependence